KOMPOSISI JENIS DAN KEPADATAN BIVALVIA DIPERAIRAN PANTAI DUSUN TANJUNG METIELLA NEGERI LIANG KECAMATAN SALAHUTU - Aneke Latuihamallo (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Ecologically, marine waters are divided into several zones, one of which is intertidal waters, where various types have adapted well to habitat conditions in various zones and types of ecosystems. The existence of bivalves plays an important role in the lives of fish and other biota that are bound to one food chain. Method: This research is a descriptive research that is to express descriptive information about bivalves in the waters of Metiella Cape. This study uses data collection techniques using the line transect method where each observation transect is drawn by a rope perpendicular to the coastline of 5 transects with a distance between each transect of 20 meters. As long as the transect is made of sample plots or quadrants with an area of ​​1 m X 1 m with a distance between each of the 5 meter quadrants, observation of the type of bivalvia is carried out in each quadrant. Results: The composition of Bivalvia found in Metiella Cape waters is 282 individuals classified in 2 sub-orders, 5 super families, 5 families, 7 genera, 8 species, namely: Pinna muricatta, Trachycardium rugosum, Fragum unedo, Mactra violacea, Tellina spengleri, Tellina timorensis, Gafrarium tumidum, Meretrix linnaeus. Conclusion: In the waters of Metiella Cape, 8 types of Bivalvia were found, namely: Fragum unedo, Trachycardium rugosum, Mactra violacea, Tellina spengleri, Tellina timorensis, Pinna muricata, Gafrarium tumidum and Meretrix linnaeus. The highest density value is found in transect II with a density value of 5.8 ind / m2 found in the type of Fredoum unedo and the lowest density value found on transect III with a density value of 0.2ind / m2 found in Mactra violacea.